Synergistic activity of Atlantic cod (Gadus morhua L.) piscidin with other antibiotic agents - Juntarut, Pongsaton (Høgskolen i Bodø, 2010)
Masteroppgave i havbruk - Høgskolen i Bodø, 2010 Disease management is crucial in the aquaculture industry and to date it involves the usage of antibiotics to treat and prevent disease, especially bacterial infections. However, there is a growing concern over the problems caused by conventional antibiotics in aquatic and terrestrial environments (eg, bacteria resistant to multiple antibiotics). Therefore, it is crucial to reduce the usage of conventional antibiotics or find alternative novel antibacterial agents to manage bacterial diseases and antibiotic-resistant bacteria. Antimicrobial peptides are natural antibiotics produced from multicellular organisms and have the ability to kill bacteria and to synergise with other antibiotics. In this study I have analysed the in-vitro antibacterial activity of synthetic Atlantic cod piscidin and its ability to permeabilize the bacterial membrane. Moreover, I have investigated the antimicrobial properties of synthetic cod piscidin in combination with several conventional antibiotics, including oxolinic acid, oxytetracycline hydrochloride, and sulfadiazine/trimethoprim, which are amongst the most important groups of antibiotics for prevention of bacterial diseases in aquaculture. Five test bacteria, including two Gram-positive bacteria (Micrococcus lysodeikticus and Planococcus citreus) and three Gram-negative bacteria (Yersinia ruckeri VI 3629, Vibrio anguillarum VI-F-258-3 and Aeromonas salmonicida NCIMB 1102) were tested for synergistic activity of peptide-antibiotic combination. Antibacterial activity results showed moderate synergism i) between oxolinic acid and synthetic cod piscidin against V. anguillarum VI-F-258-3; ii) combined oxytetracycline hydrochloride and synthetic cod piscidin against V. anguillarum VI-F- 258-3 and A. salmonicida NCIMB 1102; iii) and combined sulfadiazine/trimethoprim and synthetic cod piscidin against M. lysodeikticus, A. salmonicida NCIMB 1102, Y. ruckeri VI 3629. In contrast, no synergistic activity of either test antibiotics with ...